2009
DOI: 10.1007/s11627-009-9244-4
|View full text |Cite
|
Sign up to set email alerts
|

Cryoconservation and regeneration of axillary shoot meristems of Indigofera tinctoria (L.) by encapsulation–dehydration technique

Abstract: In vitro axillary shoot proliferation was achieved from single-node explants of Indigofera tinctoria on a welldefined medium, Murashige and Skoog (MS) medium supplemented with 1.0 mg l −1 N 6 -benzyl adenine (BA) and 0.1 mg l −1 indole-3-acetic acid. Axillary shoot meristems from cultures derived from up to three subcultures were used in the encapsulation-dehydration technique. Preconditioned, calcium alginate-encapsulated, and precultured axillary shoot meristems were subjected to different lengths of desicca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…It also enables exchange of pathogen free propagules across international borders avoiding bulk transportation of plants, quarantine and spread of diseases (Bhanuprakash 2015). As the plant conversion ability is retained even after aseptic storage under culture room conditions (25 ± 2°C) or in liquid nitrogen (-196°C) it is being used for conservation of many endangered medicinal plant species (Nair and Reghunath 2009;Maqsood et al 2012, Gantait et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…It also enables exchange of pathogen free propagules across international borders avoiding bulk transportation of plants, quarantine and spread of diseases (Bhanuprakash 2015). As the plant conversion ability is retained even after aseptic storage under culture room conditions (25 ± 2°C) or in liquid nitrogen (-196°C) it is being used for conservation of many endangered medicinal plant species (Nair and Reghunath 2009;Maqsood et al 2012, Gantait et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Also effective, but to a lesser degree was the 1 mg/L IAA with 1 mg/L BA treatment, producing 36 ± 6.82 shoots per explants. In other related studies, proper combination of cytokinin and auxin formulations have shown to be critical for shoot elongation in many other plant species for their in vitro propagation (Rout et al, 2000;Karim et al, 2003;Skala and Wysokińska, 2004;Nair and Reghunath, 2009). The correct ratio of cytokinin and auxin is important as their interaction can promote the development of shoots (Kamat and Rao, 1978).…”
Section: Resultsmentioning
confidence: 99%
“…The results show no hindrance in rooting of BAP-NAA induced shoots on I. potaninii. Reghunath (2009) andNair et al (2016) studied on I. tinctoria and noted that in vitro axillary shoot proliferation was achieved from single-node explants on MS medium containing various concentrations of 1 mg/L BA and IAA acid. Rajabudeen et al (2014) reported axillary buds of I. viscosa from nodal explants proliferated on 1 mg/L BAP and 1.5 mg/L NAA underwent multiplication of shoots.…”
Section: Discussionmentioning
confidence: 99%
“…A few in vitro culture studies have been reported for other Indigofera species like I. enneaphylla, I. potaninii, I. tinctoria, I. viscosa and I. tirta (Bharal and Rashid, 1978;Howell et al, 1986;Nair and Reghunath, 2009;Rajabudeen et al, 2014;Senthilkumar et al, 2015;Nair et al, 2016). All of them indicated that Indigofera species are highly recalcitrant.…”
mentioning
confidence: 99%